2006
DOI: 10.1021/ma060541u
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Disorder and Mesoscopic Order in Polydisperse Acrylic Block Copolymers Prepared by Controlled Radical Polymerization

Abstract: Self-assembly of high molecular weight polydisperse acrylic block copolymers and their blends is presented under conditions as close as possible to thermodynamic equilibrium. Di- and triblock copolymers comprising a poly(butyl acrylate) (PBA) first or middle block, and poly(methyl methacrylate) (PMMA) second or outer blocks, denoted MBA and MBAM, respectively, are prepared by nitroxide-mediated polymerization (NMP). Their particularity is that the acrylic block is controlled while the methacrylate block is pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
153
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(183 citation statements)
references
References 67 publications
27
153
3
Order By: Relevance
“…This phenomenon was attributed to the high miscibility of pHEMA blocks with shorter PDMS blocks. 34 This observation was in agreement with the SAXS profile of H97S3, which had primary reflection with a very low intensity.…”
Section: Dynamic Mechanical Analysissupporting
confidence: 88%
“…This phenomenon was attributed to the high miscibility of pHEMA blocks with shorter PDMS blocks. 34 This observation was in agreement with the SAXS profile of H97S3, which had primary reflection with a very low intensity.…”
Section: Dynamic Mechanical Analysissupporting
confidence: 88%
“…Although long time the idea was set that ordered microphases in block copolymers can be achieved only by a narrow dispersity, [68] some studies have demonstrated their self-assembly into well-ordered structures even presenting a broader molecular weight distribution (MWD). [69][70][71][72][73] Our starting materials for the blends exhibit, with values of 1.16 and 1.19 for neat SIM and ISM, by themselves relatively broad MWDs and as both terpolymers have unequal molecular weights the combination in a blend provides both a polydispersity in molecular weight and composition. The repulsive segmental interactions between the copolymer blocks is the driving force for microphase separation and leads them to stretch in order to adopt a minimum of interfacial contact area.…”
Section: Resultsmentioning
confidence: 95%
“…This larger interfacial thickness can be responsible of the lack of reflections. 64,65 In addition, there is other important aspect that can reduce the ordering capability at large scale in these copolymers together with the just mentioned diffuseness of the phase boundaries. This is the polydispersity (see Table 1), although the values reached are quite low, they are higher than those that can be obtained through living anionic polymerisation.…”
Section: Condensed State Properties Of the Triblock Copolymersmentioning
confidence: 99%
“…Therefore, differences in the macrochain length make difficult the development of ordered arrangements and longer annealing at temperature higher than glass transition temperature of the rigid block are often necessary to promote ordering, this being even impossible sometimes. 65 However, the amphiphilic nature of these copolymers makes the existence of self-assembly more interesting in solution than in condensed matter.…”
Section: Condensed State Properties Of the Triblock Copolymersmentioning
confidence: 99%